AKIBAT WANPRESTASI DALAM PERJANJIAN SEWA MENYEWA (Studi Kasus : Wanprestasi PadaPerjanjian Sewa Menyewa Tempat Usaha Di Pasar Kumbasari Denpasar) - Dian Ardhiyanti, A. A.; Dirksen, A. A. Gde; Putrawan, Suatra (Kertha Semaya : Journal Ilmu Hukum, 2015)
The implementation of regional autonomy, especially in Denpasar give authority to local governments to explore the sources of finance to maximize the revenues derived from its own country. Implementation of tenancy in the Kumbasari Market Denpsar conducted by Enterprise Market Area of Denpasar is a form of regional autonomy itself. This discussion is the need to deepen the legal consequencesin the event of breach of contract on the lease agreementon the business premises Kumbasari Denpasar Market.By using empirical methods to conduct research and interviews with staff Kumbasari market and traders who renta place of business in Kumbasari market, it can be seenthe agreementisan eventin which apromise to one another or where two men promised each other to carry outathing. Inanagreementis possiblein the event ofone partyis negligent incarrying out such obligation has been agreed, then the negligentparty can besaid to bea breach of contractor breach of contract. Therefore there is always aguarantee of any agreement to resolvea breach of contract.In the event of a breach of contract lease agreement on the Kumbasari market Denpasar in accordance with the provisions of the lease agreement Kumbasari Market Place of Business in Denpasar give advance warning first, than take authority or right to PD Pasar Denpasar to unilaterally cancel the lease agreement meant or in other words the breach of contract traders not allowed to sell again in Denpasar Kumbasari market.
Keywords: agreement, lease, breach of contract